Endogenous antioxidants in human skeletal muscle and adaption in energy metabolism: With reference to exercise-training, exercise-related factors and nutrition - Svensson, M. B. (2003)
The antioxidant homeostasis is determined by a wide array of interacting cellular antioxidants, as well as being influenced by the homeostasis in energy metabolism. Changes in antioxidant homeostasis, as a consequences of altered production of reactive oxygen species (ROS). and/or by changes in the resident levels of antioxidants. are likely to be involved in the overall regulation of cellular functions. Besides their obligate role in the fight against ROS, antioxidants may also function as regulators of growth factor receptors, cell-signalling reactions, or activators or in-activators of enzymes and proteins involved in transcription and translation. The metabolism of antioxidants and of reactive oxygen/nitrogen/sulphur species in a particular tissue is coupled to the local homeostasis Of 02 and energy metabolism, which are particularly stressed in human skeletal muscle during exercise. The endogenous antioxidants, ubiquinone (Q10), urate, and glutathione (GSH), which are presented in this thesis, are all differentially linked to energy metabolism and studied in terms of human skeletal muscle, exercise, training and nutrition. The results of the present studies provide several novel insights into these relationships. Thus, the level of Q1O was not influenced in muscle in response to high-intensity 'overload- training. Interestingly, the improvement of performance during training was clearly inhibited with Q1O supplementation (120 mg - day-'). Further, the increase in plasma urate levels following exercise displayed a marked adaptation in response to few days with controlled h ighintensity exercise-training, and recovery from training. Importantly. the results from the study on urate metabolism in muscle reveal that urate is produced within skeletal muscle during strenuous exercise and is extracted from blood during the recovery period. The increase in urate observed in muscle following exercise was accompanied by elevated level of allantoin, which is an oxidised product derived from urate and its reactions with ROS. Moreover, the results demonstrate that the metabolism of GSH in skeletal muscle readily adapts in response to current loads on the muscle. The observed depression of GSH in response to the exhaustive exercise was correlated to diverse parameters, such as muscle fibre type. performance and AMP deaminase activity in combination with phosphocreatine (PCr) catabolism. A complimentary in vitro study of the GSH biochemistry of primary human skeletal myoblast revealed that the sulphur amino acid precursor specificity and the capability to export GSH, in response to exposure of various hormones/hormone-mimics, were altered by differentiation of myoblast (single nucleated) into myotube-like cells (multinucleated). An unusual adaptive gain is clearly demonstrated in respect to the ability of myotube-like cells to utilise extracellular methionine to support the intra-cellular GSH synthesis, concurrently with a loss in the ability to use of extra-cellular GSH itself. Furthermore, the capability to export GSH in vitro, in response to exposure of stress hormones/hormone-mimic such as glucagon, vasopressin, and phenylephrine, was increased following differentiation. These results strongly suggest that skeletal muscle cells may provide a hormonally-regulated. extra-hepatic source of systemic GSH in the human body.